Genetic Parameters of Quantitative Characters OF Self-Produced Lines of the Fifth Generation of Corn Plants in Dry Land - I Wayan Sutresna; I Wayan Sudika; Dwi Ratna Anugrahwati (Postgraduate, University of Mataram, 2026)
This study aimed to determine the genetic diversity, heritability, and correlation of quantitative traits of the fifth generation (S5) of selfing lines of maize plants. The experiment was conducted in the dry land of Gumantar village, North Lombok, from February to May 2025. The design used in this experiment was a randomized block design. The number of treatments was 30 S5 lines. Each treatment was repeatedThe experiment was conducted twice, resulting in 60 experimental units. Eleven quantitative characters were observed, consisting of growth variables, yield components, harvest age, and yield. The experimental data were analyzed using analysis of variance at a significance level of five percent. The correlation between characters and yield was calculated using Pearson rank correlation. The results showed that six quantitative characters of the S5 line had narrow genetic diversity and six characters had moderate criteria; with genetic diversity coefficients ranging from 1.56 for harvest age and 13.02 for yield. The broad-sense heritability of 1,000-grain weight was high, six characters were moderate, and the rest were narrow. The yield character was strongly correlated with the harvested dry cob weight per plant; with cob length being moderately correlated; four characters were weakly correlated, and the other characters were not correlated with yield. The plants selected to form the sixth selfing generation were taller plants with narrower leaf angles and flowering simultaneously